2010
DOI: 10.1002/star.200900214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of starches isolated from different Chinese Baizhi (Angelica dahurica) cultivars

Abstract: Starches from three cultivars of Baizhi (Angelica dahurica; named Chuan Baizhi, Yu Baizhi, and Qi Baizhi, respectively) growing in Sichuan, Henan, and Hebei province in China were used to investigate the physicochemical properties, appearances, X‐ray powder diffraction, thermal and pasting properties. These Baizhi starch granules were in irregular polygonal shape, and their sizes range from 1 to10 µm. The average granule diameter of Chuan Baizhi, Yu Baizhi, and Qi Baizhi starches was 6.78, 8.02, and 9.09 µm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The resulting X-ray diffraction patterns of the Tartary buckwheat and common buckwheat varieties and the maize starch presented the ''A'' type pattern, as expected. The potato starch exhibited the ''B'' type X-ray diffraction pattern as expected (Jane, 2006;Zhou, Wang, Zhao, Fang, & Sun, 2010;Zobel, 1988). In the study, the results for the Tartary buckwheat starches showed the same X-ray diffraction pattern as reported by Liu et al (2013), and the starches of the common buckwheat varieties presented similar X-ray diffraction patterns to those reported by Zhang et al (2009).…”
Section: Morphological Characteristicssupporting
confidence: 88%
See 3 more Smart Citations
“…The resulting X-ray diffraction patterns of the Tartary buckwheat and common buckwheat varieties and the maize starch presented the ''A'' type pattern, as expected. The potato starch exhibited the ''B'' type X-ray diffraction pattern as expected (Jane, 2006;Zhou, Wang, Zhao, Fang, & Sun, 2010;Zobel, 1988). In the study, the results for the Tartary buckwheat starches showed the same X-ray diffraction pattern as reported by Liu et al (2013), and the starches of the common buckwheat varieties presented similar X-ray diffraction patterns to those reported by Zhang et al (2009).…”
Section: Morphological Characteristicssupporting
confidence: 88%
“…The starches of all four buckwheat varieties presented significantly higher breakdown viscosities than the potato and maize starches and the starch of the Tartary buckwheat variety Xinong9920 presented the highest breakdown viscosity at 825 cP. The viscosity variations of starch during the heating cycle are influenced by the length, granular swelling, and solubility of starch amylose as well as granule friction (Zhou et al, 2010). Setback viscosity is a measure of the stability of cooled starch paste and a high setback viscosity indicates the tendency to retrograde (Uarrota et al, 2013).…”
Section: Pasting Viscositymentioning
confidence: 93%
See 2 more Smart Citations
“…This is a major nutritional component in plant grains, consisting primarily of amylose and amylopectin. Starch has been used in numerous industrial applications around the world for thickening, stabilizing, and the gelling capabilities in a wide variety of foods and non-food products (Zhou, Wang, Zhao, Fang, & Sun, 2010). Physicochemical properties of starch differ with its source (Guinesi et al, 2006) and with the practiced extraction procedures or processes.…”
Section: Introductionmentioning
confidence: 99%